Improving science process skills using the STEM (science, technology, engineering, and mathematics) learning model on environmental preservation business material for fifth grade elementary school students - Rismawati, Ade; Kelana, Jajang Bayu; Hadianti, Yeni (Sekolah Pascasarjana UPI, 2024)
Society must be able to adapt in various ways due to the rapid progress of science and technology in the era of globalization. One of the components is education, which is fundamental for the progress of a country. Science process skills are skills for developing the perspective needed to build natural science. This research was conducted to see whether science process skills improved after applying the STEM learning model to environmental conservation business materials, in class V students at SDN 1 Ciledug located in the city of West Bandung. This research was carried out by designing a pretest-posttest group and using a science process skills test, based on the indicators that had been designed. Data analysis to determine differences in perceptions regarding improving students' science process skills, before and after implementing the STEM learning model. The results of data analysis show that science process abilities have increased on the topic of environmental conservation efforts with the application of the STEM learning model. The resulting score with the average value of science process skills increased from application of 40.51 to 85.11. This improvement in skills can be seen from the N-Gain result value of 0.75 which is in the high classification. Thus, the research results that have been presented suggest that teachers can use the STEM learning model as an alternative in science subjects, especially to improve science process skills.